"Food prices were high, and the dal became watery". Mixed-method evidence on household food insecurity and children's diets in India. (November 2018) - Aurino, Elisabetta; Morrow, Virginia
Highlights: Mixed-method study of household food insecurity and child diets in India. Food insecurity predicts lower dietary quality, especially at preschool-age. Children perceive food security and healthy diets as key for their well-being. Children value social protection, but also express concerns about implementation. Data gathered from children can help to make programmes context- and age-specific. Abstract: Food insecurity and malnutrition are key policy priorities in India. Evidence on children's experiences of household food insecurity and how food insecurity influences their dietary quality is limited for India and other low- and middle-income countries. Evidence on mid-childhood and adolescence is even scarcer. We present longitudinal evidence on household food insecurity and child diets by drawing on a mixed methods study with two cohorts of children from Andhra Pradesh and Telangana (India). Analysis of survey data shows that children living in food insecure households had lower dietary diversity and probability of consumption of micronutrient- and protein-rich foods, which are critical for their healthy development. Inequalities in child dietary quality by household food security status were most pronounced at preschool age. Children identified dietary quality as a critical dimension of their well-being. From an early age, children were able to describe and explain the food security challenges of their families and recognize the negative consequences of household food insecurity on their diets, health and education. Children were not only cognizant of household responses to food insecurity, but they were also actively involved in such strategies through limiting the quantity and quality of food purchased and consumed, reducing dietary diversity, and/or engaging in work or social protection. The latter were often mentioned as critical safety nets in face of economic, demographic or climate shocks, although children expressed criticism about implementation. Longitudinal mixed methods can enhance our understanding of children's experiences of household food insecurity and its repercussion on their health and broader well-being. Child-focused evidence is key to shaping social protection implementation to context-specific needs at critical human development stages.